The pilot study on Down to Earth (D2E) injury prevention program among varsity netball players - Zulkarnain, Jaafar (Edizioni Minerva Medica, 2019)
BACKGROUND: Sports injuries involving lower extremities have been reported to be very common in netball. We explored the effect of Down to Earth, a program which focuses on safe-landing techniques during sport activities, in reducing lower limbs injuries among varsity netball players. METHODS: This was a single-blinded controlled trial, where 42 varsity netball players were randomly assigned into two groups, the intervention group (N.=17) and the control group (N.=25). The intervention group was instructed to incorporate Down to Earth program in their training, while the control group continued to train using their standard program for 6 weeks. Data on lower extremity injury were collected during training or competition for the period of 6 weeks post intervention. RESULTS: The overall incidence of injuries was 5.9 injuries per 1000 hours of participations throughout the study. The mean exposure hour was 77 hours during training and 32 hours during match. The intention to treat analysis showed that the rate ratio ranges from 0.01-0.71. The number of training injuries were significantly higher in the control group than the intervention group (P<0.05). Based on number to treat, number of players that were needed to prevent one injury during training was three players and 37% of the players in intervention group were protected by the Down to Earth program. The intervention group had 0.01 lower rate of lower limb injury during training than the control group. CONCLUSIONS: This study has shown that Down to Earth program is beneficial in reducing the risk of lower limbs injuries during training among the varsity netball player. As previous study also reported that more training hours are advantageous for athletes to reduce injury risk, this suggests that Down to Earth could be considered as one of the effective programs for sports injuries prevention.